2020
DOI: 10.3389/fmicb.2020.01693
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Staphylococcus aureus Under the Stress Condition Caused by Litsea cubeba L. Essential Oil via RNA Sequencing

Abstract: Litsea cubeba L. essential oil (LCEO) is a natural essential oil with considerable antimicrobial activity, and it can gradually replace some chemical additives in the food industry. However, the genetic evidences of stress response of bacteria under sub-lethal treatment with LCEO is limited. To this end, transcriptomic analysis of Staphylococcus aureus 29213 under a low concentration of LCEO was performed. Bacterial RNA samples were extracted from 1/4 MIC (0.07 µL/mL) of LCEO-treated and nontreated S. aureus 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…However, we still believe that the overall trend was enhanced degradation and retarded biosynthesis of fatty acid. Because 1: in our previous work [ 19 ], LCEO caused a significant upregulation of genes related to fatty acid degradation in S . aureus ; 2: just a small proportion of genes were down-regulated in the fatty acid degradation pathway and up-regulated in the fatty acid biosynthesis pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we still believe that the overall trend was enhanced degradation and retarded biosynthesis of fatty acid. Because 1: in our previous work [ 19 ], LCEO caused a significant upregulation of genes related to fatty acid degradation in S . aureus ; 2: just a small proportion of genes were down-regulated in the fatty acid degradation pathway and up-regulated in the fatty acid biosynthesis pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, through transcriptomics, we found that toxin production and a variety of metabolic pathways of Staphylococcus aureus ( S. aureus ) were significantly affected by LCEO [ 19 ]. The objective of the present work was to detect stress reactions of MDR A. baumannii under 1/2 minimum inhibitory concentration (MIC) of LCEO using transcriptomics.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids are degraded by fatty acid degradation to generate acetyl-CoA followed by β-oxidation in the cytoplasm by activation of prokaryotic fatty acids. β-oxidation is a cyclic reaction of dehydrogenation, hydration, dehydrogenation, and thiolysis until the acyl-CoA is completely cleaved to acetyl-CoA (Yunqiao Yang et al, 2020 ). After CPA 19 treatment, the expression of some key enzymes in the β-oxidation process was downregulated, and the downregulation of these key proteins resulted in the decrease of acetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more researchers have been devoted to the study of the inhibition of plant polyphenols because of their natural and broad antibacterial properties ( Yun-Seok et al, 2010 ; Sidhu et al, 2014 ; Yang et al, 2020 ). Phenolic acids are major plant metabolites, which occur in all parts of the plant: shells, leaves, seeds, fruits, and wood parts ( Efenberger et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit is the most widely used part of L. cubeba and has a variety of biological activities. L. cubeba fruit essential oil inhibited the growth of drug-resistant Staphylococcus aureus and Acinetobacter baumannii ( 6 , 7 ). L. cubeba fruit essential oil also inhibited the expression levels of tumor necrosis factor-α (TNF-α) and IL-12 in bacterial endotoxin (lipopolysaccharide, LPS)-stimulated bone marrow-derived dendritic cells and reduced contact hypersensitivity responses in mice ( 8 ).…”
Section: Introductionmentioning
confidence: 99%